Influência da cobertura morta sôbre a umidade de um solo cultivado com cafeeiro - Brasil Sobrinho, Moacyr de O. C. do; Mello, Francisco de A. F. de (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1960)
The present paper is part of a study about the influence of mulching on some chemical and physical properties on a soil "latosolo vermelho amarelo" of a coffee plantation. The authors reported only the results obtained on soil moisture conservation and concluded that the mulching had a better effect. The results were more effective on dry weather and mainly on soil upper layer about 0 to 2 cm.